PENGARUH PEMBELAJARAN MEMBACA PEMAHAMAN CERITA FANTASI DENGAN MENGGUNAKAN DISCOVERY LEARNINGTERHADAP SISWA SMP - Agus Maulana Yusuf; Suminar Suminar; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study aims To find out the implementation of discovery learning model in learning to read the understanding of fantasy stories in junior high school students. To know the difference of learning result read the understanding of fantasy story between experimental class in junior high school students. To know the difficulties faced by students in learning to read the understanding of fantasy story by using model discovery learning in junior high school students. Research result. Discovery learning model can improve students' ability in reading comprehension learning fantasy story. It is proven that the value of pretest and post-test using discovery learning model. Judging from the pretest results, the value obtained and because the value is not reached KKM. However, after using the discovery learning model can see the value obtained by KKM. Judging from the results on the pre-test beginning and end of the obtained values on average and 58 and 67 and at post-test 76 and 79.